Cloning, Characterization, and Functional Expression of Phospholipase Dα cDNA from Banana (Musa acuminate L.). (22nd October 2017) - Li, Li; He, Xuemei; Sun, Jian; Li, Changbao; Ling, Dongning; Sheng, Jinfeng; You, Xiangrong; Li, Jiemin; Liu, Guoming; Zheng, Fengjin; Tang, Yayuan
Abstract : Phospholipase D (PLD) plays a key role in adaptive responses of postharvest fruits. A cDNA clone of banana ( Musa acuminate L.) PLDα ( M a P L D α ) was obtained by RT-PCR in this study. The MaPLDα gene contains a complete open reading frame (ORF) encoding a 92-kDa protein composed of 832 amino acid residues and possesses a characteristic C2 domain and two catalytic H×K×××D (abbr. HKD) motifs. The two HKD motifs are separated by 341 amino acid residues in the primary structure. Relatively higher PLD activity and expression of MaPLDα mRNA were detected in developing tissues compared to senescent or mature tissues in individual leaves, flower, stem, and fruit organs, respectively. The expression profile of PLDα mRNA in postharvest banana fruits at different temperatures was determined, and the MaPLDα mRNA reached the highest expression peak on day 5 at 25°C and on day 7 at 12°C. The results provide useful information for maintaining postharvest quality and extending the storage life of banana fruit.